A lamellar V2O3@C composite for aluminium-ion batteries displaying long cycle life and low-temperature tolerance. Issue 51 (7th June 2022) - Han, Tianli; Wang, Yan; Bai, Haiyuan; Zhang, Huigang; Liu, Jinyun
Abstract : A lamellar composite composed of V2 O3 @C nanosheets is developed as an Al-ion battery cathode, which displays long cycling life and stable electrochemical performance at a low temperature. Abstract : Rechargeable aluminum-ion (Al-ion) batteries have important potential for fast charging and safe energy-storage systems. Here, we develop a composite composed of lamellar V2 O3 @C nanosheets, which displays high electrochemical properties as an Al-ion battery cathode. The unique structure is conducive to the rapid insertion and release of Al 3+ ions, electrolyte infiltration, and improved conductivity. After cycling 500 times, the capacity exceeds 242.5 mA h g −1 . Under a low temperature of −10 °C, the capacity remains 150.8 mA h g −1, and the Coulombic efficiency is higher than 98.8%. The V2 O3 @C also exhibits a good reversibility verified by using ex situ X-ray powder diffraction patterns, while the constant current intermittent titration technology shows a low reaction barrier, which indicates that the lamellar composite presented here could find significant applications for engineering many high-performance energy-storage systems.